(untitled) (Vietnam Journal of Community Medicine, 2024)
Overview: Laparoscopic surgery placing a completely preperitoneal mesh [Total Extra-Peritoneal (TEP) Inguinal Hernia Repair] has been applied for a long time and has become an important technique in the treatment of inguinal hernia. Notwithstanding being a safe method with a low complication rate, there are few studies evaluating factors associated with the risk of near and far complications after surgery. Aim: To evaluate treatment results and risk factors that increase complications after surgery. Methods: A retrospective study on 30 patients undergoing inguinal hernia surgery using the TEP technique was conducted at Hanoi Medical University Hospital. All subjects participating in the study were clinically examined with ultrasound 1 month later and had follow-up results at least 3 months after surgery. Results: No patient had complications during surgery. Early postoperative complications encountered were mainly inguinal and scrotal pain (26.7%) and fluid collection (10%). The most common distant complication was scrotal paresthesia, seen in 36.7% of patients. Multivariable logistic regression model showed that patients with overweight status (BMI > 24.9 kg/m2) were often at risk of complications after TEP surgery at 1 month (OR = 2.3; p = 0.04) and higher long-term complications (OR = 2.2; p = 0.04). In addition, proximal complications increased the risk of distant complications by 2.5 times (OR=2.5; p=0.03). Conclusion: TEP inguinal hernia repair is a safe and effective treatment remedy.